2013
DOI: 10.1016/j.triboint.2012.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Pin-on-disc study of the effects of railway friction modifiers on airborne wear particles from wheel–rail contacts

Abstract: Knowledge of wheel-rail interaction is crucial to wheel and rail maintenance. In this interaction, some of the worn-off material is transformed into airborne particles. Although such wear is well understood, few studies treat the particles generated. We investigated friction modifiers' effects on airborne particles characteristics generated in wheel-rail contacts in laboratory conditions. Pin-on-disc machine testing with a round-head pin loaded by a dead weight load 40 N simulated maximum contact pressure over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 35 publications
(25 citation statements)
references
References 13 publications
(15 reference statements)
0
25
0
Order By: Relevance
“…However, the laboratory results presented by Sundh et al (2009), Abbasi et al (2011Abbasi et al ( , 2012bAbbasi et al ( , 2013, and Olofsson (2010) indicate that UFPs are also generated by wear processes involving rail, wheel, and braking materials. They reported that the particle concentration in coarse, fine and ultrafine regions are dependent on the contact conditions of mating surfaces (i.e sliding velocity, contact pressure, temperature lubricant and material properties).…”
Section: Discussionmentioning
confidence: 99%
“…However, the laboratory results presented by Sundh et al (2009), Abbasi et al (2011Abbasi et al ( , 2012bAbbasi et al ( , 2013, and Olofsson (2010) indicate that UFPs are also generated by wear processes involving rail, wheel, and braking materials. They reported that the particle concentration in coarse, fine and ultrafine regions are dependent on the contact conditions of mating surfaces (i.e sliding velocity, contact pressure, temperature lubricant and material properties).…”
Section: Discussionmentioning
confidence: 99%
“…These particles can be found in a higher concentration when the sliding velocity of the test run was increased. Abbasi et al [29] investigated friction modifiers' effects on airborne particles characteristics generated in wheel-rail contacts in laboratory conditions. The same test set up as Sundh and Olofsson [27] was used with the addition of an aerosol instrument that could measure particles down to 10 nm (SMPS).…”
Section: Particle Measurements From Laboratory Experimentsmentioning
confidence: 99%
“…These data represent the size distribution of particles in the 10 < dp < 540 nm interval recorded using an SMPS. [29] . These data represent the size distribution of particles in the 10 < dp < 540 nm interval recorded using an SMPS [29].…”
Section: Particle Measurements From Laboratory Experimentsmentioning
confidence: 99%
See 2 more Smart Citations